Dwarfing and Freeze Hardiness Potential of Trifoliate Orange Rootstocks - James J. Ferguson; Jose Chaparro (EDIS, 2004)
While Flying Dragon has shown some promise as a freeze hardy and dwarfing rootstock, questions often arise about its rootstock genetics, rootstock/scion interactions, and cultural practices that can affect tree size. Accordingly, the purpose of this fact sheet is to discuss these issues as they relate to trifoliate orange rootstocks, especially Flying Dragon. This document is HS982, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 2004.